Mastering Microsoft Visual basic 2005 - Petroutsos, Evangelos (Wiley Pub, 2006)
Part 1: GUI Design and Event-Driven Programming. Chapter 1: Getting Started with Visual Basic 2005. Chapter 2: Visual Basic: The Language. Chapter 3: Procedures and Modules. Part 2: Building Rich Client Applications. Chapter 4: Basic Windows Controls. Chapter 5: Working with Forms. Chapter 6: More Windows Controls. Chapter 7: The TreeView and ListView Controls. Part 3: Programming with Objects. Chapter 8: Building Custom Classes. Chapter 9: Working with Objects. Chapter 10: Interfaces and Delegates. Chapter 11: Building Custom Windows Controls. Part 4: Working with the .NET Framework. Chapter 12: Handling Strings, Characters, and Dates. Chapter 13: Storing Data in Collections. Chapter 14: Accessing Folders and Files. Chapter 15: Data Encryption. Chapter 16: Serialization and XML. Chapter 17: Working with XML. Part 5: Drawing and Printing. Chapter 18: Drawing and Painting with Visual Basic 2005. Chapter 19: Manipulating Images and Bitmaps. Chapter 20: Printing with VB 2005. Part 6: Database Programming with VB 2005. Chapter 21: Basic Concepts of Relational Databases. Chapter 22: Visual Database Tools. Chapter 23: Programming the ADO.NET Objects. Chapter 24: Working with SQL Server 2005. Chapter 25: Typical Data-Driven Applications. Part 7: Programming for the Web. Chapter 26: Developing for the Web. Chapter 27: ASP.NET 2.0. Chapter 28: Developing Data-Driven Web Applications. Chapter 29: XML Web Services. Part 8: Polishing Your Applications. Chapter 30: Designing Functional, Professional Interfaces. Chapter 31: Error Handling and Debugging. Chapter 32: Application Deployment. Index.